(untitled) (Praxis Educativa, 2021)
Integral practices constitute instances of undergraduate training and articulation with the community. In this framework, it is possible to integrate the traditions of research, extension and teaching from a dialogic and constructivist paradigm in a pedagogical scheme that, in addition, allows addressing the problems that cross the territory. The success of the format depends on efficient management, that is why planning that guarantees its objectification and permanent evaluation is important. Context, problematization, diagnosis, objectives, goals, methodology (which includes activities, dynamics and resources) and tools, for a situational strategic planning and evaluation, constitute some of the categories that allow designing the format in which teaching is objectified.